2011
DOI: 10.1016/j.str.2011.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Adenosine A2A Receptor in Complex with ZM241385 and the Xanthines XAC and Caffeine

Abstract: Methylxanthines, including caffeine and theophylline, are among the most widely consumed stimulant drugs in the world. These effects are mediated primarily via blockade of adenosine receptors. Xanthine analogs with improved properties have been developed as potential treatments for diseases such as Parkinson's disease. Here we report the structures of a thermostabilized adenosine A(2A) receptor in complex with the xanthines xanthine amine congener and caffeine, as well as the A(2A) selective inverse agonist ZM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
584
1
16

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 513 publications
(651 citation statements)
references
References 47 publications
29
584
1
16
Order By: Relevance
“…Furthermore, specific actions of caffeine, including increased arousal (Huang et al, 2005), increased locomotor activity (El Yacoubi et al, 2000) and increased ethanol tolerance can be attributed to its inhibition of A2AR. In addition, a recent co-crystal structural study has revealed that ZM241385 (A2AR specific antagonist) and caffeine have similar pharmacological binding properties to A2AR (Dore et al, 2011), suggesting that inhibition of A2AR by either ZM241385 or caffeine might enhance goal-directed behavior and promote ethanol drinking (Fig. 2).…”
Section: A2ar Inhibition In the Dms And Goal Directed Drinkingmentioning
confidence: 99%
“…Furthermore, specific actions of caffeine, including increased arousal (Huang et al, 2005), increased locomotor activity (El Yacoubi et al, 2000) and increased ethanol tolerance can be attributed to its inhibition of A2AR. In addition, a recent co-crystal structural study has revealed that ZM241385 (A2AR specific antagonist) and caffeine have similar pharmacological binding properties to A2AR (Dore et al, 2011), suggesting that inhibition of A2AR by either ZM241385 or caffeine might enhance goal-directed behavior and promote ethanol drinking (Fig. 2).…”
Section: A2ar Inhibition In the Dms And Goal Directed Drinkingmentioning
confidence: 99%
“…To date, most crystallization studies are focused on indirect uses, such as expression or stability screening, to facilitate higher throughput in a short period of time. The best example of this was provided by the Tate group in solving the crystal structures of the β1 adrenergic receptor and the A 2A adenosine receptor in the active state [16,37] . All of the mutants were expressed in E coli using a procedure that is similar to Grisshammer's, and the construct optimization was performed accordingly, before the final transfer to insect cells for large-scale preparations.…”
Section: E Colimentioning
confidence: 99%
“…The most promising mutations were then combined and further screened for the highest stability to tolerate the harsh environment during extraction, purification and crystalliza tion [38,45] . Guided by this method, they solved the crystal structures of the β1 adrenergic receptor with different ligands and the A 2A adenosine receptor structure in an active state [4,16] . Similarly, PLÜCKTHUN et al used error-prone PCR (epPCR) to construct a library of mutations of target gene which were expressed and sorted by flow cytometry to screen for higher expression or stability.…”
Section: Mutationsmentioning
confidence: 99%
See 2 more Smart Citations